Optimizing Temperature and Time for Producing Coconut Shell Activated Charcoal to Reduce Free Fatty Acids in Used Cooking Oil - Dio Ajeng Oktavian; Rini Kartika Dewi (Universitas Islam Raden Rahmat, Malang, 2025)
Activated charcoal is a type of carbon that has a high capacity to absorb anions, cations, and molecules in both organic and inorganic compounds, whether in solutions or gases. This research aims to determine the effect of temperature variation and carbonization time on optimizing the production of activated charcoal from coconut shells as an environmentally friendly solution to reduce the acid value in used cooking oil. The activated charcoal production process in this study uses carbonization with temperature variations of 200°C, 250°C, 300°C, and 350°C, and carbonization times of 1 hour, 1.5 hours, 2 hours, 2.5 hours, and 3 hours. The best results for activated charcoal are obtained at 350°C and 3 hours, with moisture content of 0.811%, volatile matter of 5.926%, ash content of 1%, and other parameters that meet the Indonesian National Standard (SNI) for activated charcoal, such as fixed carbon content, iodine absorption capacity in accordance with SNI-06-3730-1995, and an acid value that also meets the standard (SNI 01-3741-2013).